Topological duality for distributive lattices theory and applications - Gehrke, Mai; Gool, Sam van (Cambridge University Press, 2024)
Introducing Stone-Priestley duality theory and its applications to logic and theoretical computer science, this book equips graduate students and researchers with the theoretical background necessary for reading and understanding current research in the area. After giving a thorough introduction to the algebraic, topological, logical, and categorical aspects of the theory, the book covers two advanced applications in computer science, namely in domain theory and automata theory. These topics are at the forefront of active research seeking to unify semantic methods with more algorithmic topics in finite model theory. Frequent exercises punctuate the text, with hints and references provided
Title from publisher's bibliographic system (viewed on 16 Feb 2024)
Keywords: Lattices, Distributive / Textbooks; Duality theory (Mathematics) / Textbooks